Evaluación in vitro de la actividad inhibitoria de aceites esenciales y sus mezclas (Curcuma longa, Cymbopogon citratus, ocotea quixos, melaleuca armillaris, zingiber officinale) en aeromona hydrophila, aeromona salmonicida y Pseudomona fluorescens - Ortega Mayorga, Cristhian Alexander (2018)
The use of antibiotics in the aquaculture industry has brought problems of bacterial and environmental resistance, facts that have forced to look for natural alternatives for the treatment of diseases produced by bacteria, being an important option the essential oils given their potential antimicrobial characteristics that help to develop sustainable aquaculture. In the research, the minimum inhibitory concentration was determined by the technique of microdilution of essential oils (Curcuma longa, Cymbopogon citratus, Ocotea quixos, Melaleuca armillaris and Zingiber officinale) and their binary and ternary mixtures on three common bacteria that cause diseases in water fish. The analysis of the composition of the essential oils was carried out by gas chromatography coupled to masses (GC-MS), being able to determine the percentage composition of each component of the oils analyzed. For Aeromona salmonicida a MIC of 0.075 mg / mL was obtained, which corresponds to Cymbopogon citratus classified as a strong activity treatment. In Aeromona hydrophila a MIC of 1.25 mg / mL classified as a moderate activity corresponding to the mixture of oils: Cymbopogon citratus and Ocotea quixos. For Pseudomonas fluorescens, a MIC of 5mg / mL was determined, corresponding to moderate activity in the mixture of Curcuma longa, Ocotea quixos and Zingiber officinale oils. It was determined that the majority of mixed oils had a partial synergism and effect of addition, only the mixture Zingiber officinale, Ocotea quixos and Melaleuca armillaris showed total synergism.